Reduced NGF Level Promotes Epithelial–Mesenchymal Transition in Human Lens Epithelial Cells Exposed to High Dexamethasone Concentrations. (2nd June 2020) - Hah, Young-Sool; Yoo, Woong-Sun; Seo, Seong-Wook; Chung, Inyoung; Kim, Hyun-A; Cho, Hee Young; Kim, Seong-Jae
ABSTRACT: Purpose : To investigate the protective effects of nerve growth factor (NGF) against steroid-induced cataract formation in dexamethasone (Dex)-treated human lens epithelial B-3 (HLE-B3) cells and the possible molecular mechanisms underlying this protection. Materials and Methods : HLE-B3 cells were treated with Dex, and cell viability was assessed using the Cell Counting Kit-8 (CCK-8) assay. The levels of expression of NGF, fibronectin, α-smooth muscle actin (α-SMA), and E-cadherin mRNAs were measured by real-time quantitative polymerase chain reaction (qPCR), and the levels of NGF, fibronectin, α-SMA, E-cadherin, tropomyosin receptor kinase A (TrkA), and Akt proteins were measured by Western blot analysis. Gene expression profiles of growth factors in Dex-treated HLE-B3 cells were determined by PCR arrays. In addition, anterior capsule tissue was obtained during cataract surgery, and the specimens were also examined expressions of NGF. Results : NGF was expressed in HLE-B3 cells and also in lens epithelial cells of anterior lens capsules. Dex treatment of HLE-B3 cells increased their expression of epithelial–mesenchymal transition (EMT) markers and migration activity, while markedly downregulating the expression of NGF. NGF treatment significantly reduced the expression of α-SMA and fibronectin, as well as cell proliferation. The decreased phosphorylation of p38 MAPK and Akt induced by Dex treatment was significantly reversed by treatment with NGF. Conclusion : NGF/TrkA may repress EMT by targeting the p38 MAPK and pAkt pathways in Dex-treated HLE-B3 cells. NGF may be a novel therapeutic target for patients with steroid-induced cataract.